What Lies Behind Successful Regulation? A Qualitative Evaluation of Pilot Implementation of Kenya's Health Facility Inspection Reforms - Eric Tama; Irene Khayoni; Catherine Goodman; Dosila Ogira; Timothy Chege; Njeri Gitau; Francis Wafula (Kerman University of Medical Sciences, 2022)
Background  Health facility regulation in low- and middle-income countries (LMICs) is generally weak, with potentially serious consequences for safety and quality. Innovative regulatory reforms were piloted in three Kenyan counties including: a Joint Health Inspection Checklist (JHIC) synthesizing requirements across multiple regulatory agencies; increased inspection frequency; allocating facilities to compliance categories which determined warnings, sanctions and/or time to re-inspection; and public display of regulatory results. The reforms substantially increased inspection scores compared with control facilities. We developed lessons for future regulatory policy from this pilot by identifying key factors that facilitated or hindered its implementation. Methods  We conducted a qualitative study to understand views and experiences of actors involved in the one-year pilot. We interviewed 77 purposively selected staff from the national, county and facility levels. Data were analyzed using the framework approach, identifying facilitating/hindering factors at the facility, inspection system, and health system levels. Results  The joint health inspections (JHIs) were generally viewed as fair, objective and transparent, which enhanced their perceived legitimacy. Interactions with inspectors were described as friendly and supportive, in contrast to the punitive culture of previous inspections when bribery had been common. Inspector training and use of an electronic checklist were strongly praised. However, practical challenges with transport, route planning and budgets highlighted the critical nature of strong logistical management. The effectiveness of inspection in improving compliance was hampered by limitations in related systems, particularly facility licensing, enforcement of closures and, in the public sector, control of funds. However, an inclusive reform development process had led to high buy-in across regulatory agencies which was key to the system's success. Conclusion  Effective facility inspection involves more than "hardware" such as checklists, protocols and training. Cultural, relational and institutional "software" are also crucial for legitimacy, feasibility of implementation and enforceability, and should be carefully integrated into regulatory reforms.